Feet of clay Selected Spring Loaded performances reviewed - Hansen, Sophie (Dance Books Ltd., Alton,Hampshire (UK), 1998)
PALABRAS CLAVE: Spring Loaded Festival, 1998, Motionhouse, Bedlam Dance Company, Yael Flexer, Rachel Krische, No. 3, Miranda Pennell, Lounge, Habit, Home Fires Burning, Clare Russ, Gourmet, In the Third Person, Faking It's.